Emerging drugs of abuse: current perspectives on substituted cathinones - Paillet-Loilier M; Cesbron A; Le Boisselier R; Bourgine J; Debruyne D (Substance Abuse and Rehabilitation, 2014)
Magalie Paillet-Loilier,1 Alexandre Cesbron,1 Reynald Le Boisselier,2 Joanna Bourgine,1 Danièle Debruyne1,2 1Toxicology and Pharmacology Laboratory, 2Centre d'Evaluation et d'Information sur la Pharmacodépendance – Addictovigilance (CEIP-A), Department of Pharmacology, University Hospital Centre, Caen, France Abstract: Substituted cathinones are synthetic analogs of cathinone that can be considered as derivatives of phenethylamines with a beta-keto group on the side chain. They appeared in the recreational drug market in the mid-2000s and now represent a large class of new popular drugs of abuse. Initially considered as legal highs, their legal status is variable by country and is rapidly changing, with government institutions encouraging their control. Some cathinones (such as diethylpropion or pyrovalerone) have been used in a medical setting and bupropion is actually indicated for smoking cessation. Substituted cathinones are widely available from internet websites, retail shops, and street dealers. They can be sold under chemical, evocative or generic names, making their identification difficult. Fortunately, analytical methods have been developed in recent years to solve this problem. Available as powders, substituted cathinones are self-administered by snorting, oral injestion, or intravenous injection. They act as central nervous system stimulants by causing the release of catecholamines (dopamine, noradrenaline, and serotonin) and blocking their reuptake in the central and peripheral nervous system. They may also decrease dopamine and serotonin transporter function as nonselective substrates or potent blockers and may inhibit monoamine oxidase effects. Nevertheless, considerable differences have been found in the potencies of the different substituted cathinones in vitro. Desired effects reported by users include increased energy, empathy, and improved libido. Cardiovascular (tachycardia, hypertension) and psychiatric/neurological signs/symptoms (agitation, seizures, paranoia, and hallucinations) are the most common adverse effects reported. Severe toxicity signs compatible with excessive serotonin activity, such as hyperthermia, metabolic acidosis, and prolonged rhabdomyolysis, have also been observed. Reinforcing potential observed in animals predicts a high potential for addiction and abuse in users. In case of overdose, no specific antidote exists and no curative treatment has been approved by health authorities. Therefore, management of acute toxic effects is mainly extrapolated from experience with cocaine/amphetamines. Keywords: substituted cathinones, chemistry, analysis, pharmacology, toxicology, dependence, medical care